The Effect of Occupational Noise Levels on Hearing among Cement Factory Workers in Tema - Arthur, J. (University of Ghana, 2016)
Noise pollution is a global occupational health issue affecting the well-being of workers who are exposed to it. A common detrimental effect of work place noise exposure over time is noise induced hearing loss. Noise induced hearing loss is completely preventable, especially when safety measures are taken, however it becomes irreversible once acquired. The main aim of the study was to determine the effect of occupational noise levels on hearing among cement factory workers. A cross-sectional study design was employed in the study. A total of 132 male participants working at the production unit of the Ghana Cement Company were conveniently sampled. A modified questionnaire was administered to obtain scientific and personal data from the participants. Otoscopy and tympanometry were done to rule out ear pathologies of all the participants. Hearing acuity of participants was assessed using pure- tone audiometry. Data analysis and data entries were done using SPSS version 20.0 and Excel word. Results were presented in tables and a p-value < 0.05 was considered to be significant. From the study, all recruited participants (100%) were knowledgeable on the effect of occupational noise levels on hearing. Majority of the participants (56.1%) used hearing protection devices, however this was irregularly used at work. The prevalence of hearing loss was greater among workers from the milling unit than workers from the packing unit at PTA512 and PTA346. The prevalence of loss in the right and left ears for workers from the milling unit were 23.5% and 29.4% respectively while that for the packing unit was 20.4% in both ears. There was no significant association between work duration and hearing loss (p> 0.05) for the right and left ears. Age was the only independent variable which significantly predicted hearing loss in both ears at PTA346 (p< 0.05). Regular audiometric testing of staff was necessary to identify individuals with threshold shifts
Theses (MSc) - University of Ghana, 2016
Keywords: Noise-induced hearing loss; occupational noise-induced hearing loss; occupational noise; cement workers; personal protective equipment